Performance-Based Government Bureaucracy - Marthina Raga Lay; Jacob Wadu (Green Publisher Indonesia, 2026)
Globalization and the development of the free market have created significant challenges for government institutions to improve their effectiveness, accountability, and responsiveness in providing public services. Traditional bureaucratic systems are often criticized for being rigid, inefficient, and less responsive to societal needs. Therefore, the concept of performance-based government bureaucracy has emerged as an important approach to improve the quality of governance and public service delivery. This study aims to examine the concept of performance-based government bureaucracy and identify strategic efforts needed to realize high-performance government institutions. This research uses a qualitative approach with a library research method. Data were collected from various sources, including books, scientific journals, government regulations, and previous studies related to public administration, bureaucracy, and performance management. The collected data were analyzed using qualitative descriptive analysis through stages of data reduction, classification, interpretation, and synthesis of relevant literature. The results of the study indicate that realizing performance-based government bureaucracy requires several strategic efforts, including organizational restructuring, development of an objective performance measurement system, responsiveness to community demands, cultivation of an entrepreneurial spirit within government institutions, creation of a continuous learning climate, and consistent leadership. These factors are essential to improve organizational effectiveness, accountability, and service quality. In conclusion, the implementation of performance-based bureaucracy is an important step toward achieving good governance. The success of this transformation depends on the commitment of government institutions to adopt performance-oriented management, strengthen organizational capacity, and integrate good governance principles into bureaucratic practices.